Tantrum Management Strategies for Early Childhood Education: A Descriptive Study in PAUD Permata Ibu and TKS IT Misbahul Ikhlas - Rizka, Sitti Muliya; Melizar , Risa; Mandira, Gracia; Fauzia, Siti Naila; Nessa, Rahmatun; Sofyan, Rahmi (The Future of Education Journal, 2024)
Tantrums are a common behavioral issue in early childhood, characterized by intense and excessive emotional outbursts that occur in specific situations. These episodes often reflect the child's limited ability to articulate needs or emotions verbally. This study aimed to identify and analyze the strategies employed by teachers in managing tantrum behaviors among early childhood learners at PAUD Permata Ibu and TKS IT Misbahul Ikhlas in Aceh Besar. A qualitative descriptive approach was used in this research, employing observation, interviews, and documentation as data collection methods. The subjects of the study were four teachers from Class A in early childhood education institutions, with the object of the research focusing on the strategies these teachers implemented in managing tantrums.The findings revealed that teachers use structured and empathetic methods, allowing children to express emotions under close supervision. Once calm, teachers engage in gentle communication to address the root of the tantrum and guide children toward better behavior by explaining consequences. Emotional bonding, such as hugs or gentle touches, provides comfort, while corrective actions, like marking fingers with tape to deter harmful behavior, remain educational. Teachers also redirect attention to positive activities and provide encouragement to boost confidence and emotional regulation. These strategies highlight the importance of patience, empathy, and tailored approaches to foster emotional growth and self-control in young children.